The Probiotic Escherichia coli Strain Nissle 1917 Combats Lambdoid Bacteriophages stx and λ - Bury, Susanne; Soundararajan, Manonmani; Bharti, Richa; von Bünau, Rudolf; Förstner, Konrad U.; Oelschlaeger, Tobias A. (Frontiers in Microbiology, 2018)
Shiga toxin (Stx) producing E. coli (STEC) such as Enterohemorrhagic E. coli (EHEC) are the major cause of foodborne illness in humans. In vitro studies showed the probiotic Escherichia coli strain Nissle 1917 (EcN) to efficiently inhibit the production of Stx. Life threatening EHEC strains as for example the serotype O104:H4, responsible for the great outbreak in 2011 in Germany, evolutionary developed from certain E. coli strains which got infected by stx2-encoding lambdoid phages turning the E. coli into lysogenic and subsequently Stx producing strains. Since antibiotics induce stx genes and Stx production, EHEC infected persons are not recommended to be treated with antibiotics. Therefore, EcN might be an alternative medication. However, because even commensal E. coli strains might be converted into Stx-producers after becoming host to a stx encoding prophage, we tested EcN for stx-phage genome integration. Our experiments revealed the resistance of EcN toward not only stx-phages but also against lambda-phages. This resistance was not based on the lack of or by mutated phage receptors. Rather it involved the expression of a phage repressor (pr) gene of a defective prophage in EcN which was able to partially protect E. coli K-12 strain MG1655 against stx and lambda phage infection. Furthermore, we observed EcN to inactivate phages and thereby to protect E. coli K-12 strains against infection by stx- as well as lambda-phages. Inactivation of lambda-phages was due to binding of lambda-phages to LamB of EcN whereas inactivation of stx-phages was caused by a thermostable protein of EcN. These properties together with its ability to inhibit Stx production make EcN a good candidate for the prevention of illness caused by EHEC and probably for the treatment of already infected people.